Remote teaching in the Covid-19 pandemic and the challenges and opportunities in the view of teachers from schools in the interior of Mato Grosso (Research, Society and Development, 2022)
This study aimed to discuss and understand the challenges and opportunities that remote teaching in a time of pandemic provided to a group of teachers from a public school in the state of Mato Grosso. The research participants were a group of teachers from different locations and schools in the interior of the State of Mato Grosso. Participants answered a questionnaire via google forms, containing open and closed questions. Data analysis was performed using the inductive method. This study shows that the opportunities experienced were related to learning the use of digital resources for teaching and the experience of getting to know the students better, which, in the view of the participants, make teaching more human. The challenges in the view of teachers ranged from teacher training to access to these technologies that made remote teaching possible. These results show that even being in the era of technology, remote teaching brought challenges when starting to use digital technologies in the context of remote teaching, as many of the teachers did not have training focused on the use of the virtual learning environment (VLE). So many teachers used several resources, being these, the one that had greater domain, such as: instant messaging application, videos, VLE and others. Finally, the present study shows that remote teaching enabled new learning about digital technologies for teachers and having as one of the main challenges in the offer of remote teaching, to attract the attention and assiduity of students during classes.